Sodium-calcium exchanger and R-type Ca(2+) channels mediate spontaneous [Ca(2+)]i oscillations in magnocellular neurones of the rat supraoptic nucleus - Kortus, Stepan; Srinivasan, Chinnapaiyan; Forostyak, Oksana; Zapotocky, Martin; Ueta, Yoichi; Sykova, Eva; Chvatal, Alexandr; Verkhratsky, Alexei; Dayanithi, Govindan (Cell calcium, 2016)
Isolated supraoptic neurones generate spontaneous [Ca(2+)]i oscillations in isolated conditions. Here we report in depth analysis of the contribution of plasmalemmal ion channels (Ca(2+), Na(+)), Na(+)/Ca(2+) exchanger (NCX), intracellular Ca(2+) release channels (InsP3Rs and RyRs), Ca(2+) storage organelles, plasma membrane Ca(2+) pump and intracellular signal transduction cascades into spontaneous Ca(2+) activity. While removal of extracellular Ca(2+) or incubation with non-specific voltage-gated Ca(2+) channel (VGCC) blocker Cd(2+) suppressed the oscillations, neither Ni(2+) nor TTA-P2, the T-type VGCC blockers, had an effect. Inhibitors of VGCC nicardipine, ω-conotoxin GVIA, ω-conotoxin MVIIC, ω-agatoxin IVA (for L-, N-, P and P/Q-type channels, respectively) did not affect [Ca(2+)]i oscillations. In contrast, a specific R-type VGCC blocker SNX-482 attenuated [Ca(2+)]i oscillations. Incubation with TTX had no effect, whereas removal of the extracellular Na(+) or application of an inhibitor of the reverse operation mode of Na(+)/Ca(2+) exchanger KB-R7943 blocked the oscillations. The mitochondrial uncoupler CCCP irreversibly blocked spontaneous [Ca(2+)]i activity. Exposure of neurones to Ca(2+) mobilisers (thapsigargin, cyclopiazonic acid, caffeine and ryanodine); 4-aminopyridine (A-type K(+) current blocker); phospholipase C and adenylyl cyclase pathways blockers U-73122, Rp-cAMP, SQ-22536 and H-89 had no effect. Oscillations were blocked by GABA, but not by glutamate, apamin or dynorphin. In conclusion, spontaneous oscillations in magnocellular neurones are mediated by a concerted action of R-type Ca(2+) channels and the NCX fluctuating between forward and reverse modes.
Keywords: Neurons; Plasma membrane calcium pump; Sarcoendoplasmic reticulum Ca(2+)-ATPase; biologický transport; Neurotransmitter Agents; Ca(2+) imaging; nucleus supraopticus; Ion Channel Gating; Glutamate; Intracellular Space; neurotransmiterové látky; Ca(2+) homeostasis; Ca(2+) signalling; Voltage-gated Ca(2+) channels; Biological Transport; Ca(2+) clearance; Transgenic rats; vápník; Calcium Signaling; mužské pohlaví; Rats, Wistar; Type C Phospholipases; Vasopressin; Oxytocin; vápníkové kanály - typ R; pumpa pro výměnu sodíku a vápníku; Calcium; adenylátcyklasy; Hypothalamus; systémy druhého messengeru; vápníková signalizace; zvířata; fosfolipasy typu C; Sodium-Calcium Exchanger; Tetrodotoxin; 1,4,5-Trisphosphate; Potassium Channels; draslíkové kanály; neurony; sodíkové kanály; intracelulární prostor; Supraoptic Nucleus; Ca(2+) channel toxins; Second Messenger Systems; sodík; Mitochondria; gating iontového kanálu; Adenylyl Cyclases; potkani Wistar; Calcium Channels, R-Type; GABA; Na(+)/Ca(2+) exchanger; Sodium; Sodium Channels; Ca(2+) oscillations; Supraoptic nucleus; Male; Animals